2019
DOI: 10.1371/journal.pone.0217667
|View full text |Cite|
|
Sign up to set email alerts
|

Development of rice conidiation media for Ustilaginoidea virens

Abstract: Rice false smut, caused by the ascomycete Ustilaginoidea virens, is a serious disease of rice worldwide. Conidia are very important infectious propagules of U. virens, but the ability of pathogenic isolates to produce conidia frequently decreases in culture, which influences pathogenicity testing. Here, we developed tissue media with rice leaves or panicles that stimulate conidiation of U. virens. Among the tested media, 0.10 g/ml panicle medium was most efficient for conidiation. Whereas, some rice leaf media… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In order to survive and complete infection, U. virens fungus needs to adapt to various stresses from the host and environment [ 35 ]. By RNA-seq analysis, we found that a lot of stress response-related genes were affected extensively when UvKMT6 was deleted (Table S3 and S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to survive and complete infection, U. virens fungus needs to adapt to various stresses from the host and environment [ 35 ]. By RNA-seq analysis, we found that a lot of stress response-related genes were affected extensively when UvKMT6 was deleted (Table S3 and S4).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, an epigenetic regulator UvKmt6 was found to contribute to the virulence of U. virens in several ways. First, disruption of UvKMT6 resulted in drastic decrease in conidiation, which usually leads to reduced pathogenicity in U. virens [ 35 ]. For example, UvAtg8 is an autophagy marker, and its gene deletion mutant is significantly reduced in pathogenicity due to the decrease of conidia production [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, such knowledge is not available in the literature. Traditionally, sufficient secondary sporidia are collected from PDA after 3 or more weeks of incubation because the fungus grows slowly, and the colonies are small even after 2 or 3 weeks of growth (Wang et al 2019). The results of our study demonstrated that the incubation time effect was significant on the production of secondary sporidia and that the most effective incubation time to produce greatest secondary sporidia was at 2 weeks, as conidial production significantly declined after 2 weeks of incubation.…”
Section: Discussionmentioning
confidence: 59%
“…Carbon source is essential for the growth and sporulation of fungi, and different carbon sources affect their ability to grow and sporulate. In previous studies, dextrose or sucrose amended liquid medium was the most common culture media used to promote fungal conidial production for inoculation preparations (Ghahal et al 1993;Wang et al 2019). Other than dextrose, however, there have been no reports on the effects of carbon sources on mycelium growth and spore production of T. barclayana.…”
Section: Discussionmentioning
confidence: 99%
“…For conidiation tests, five mycelial plugs were incubated in 50 mL YT (YTA without agar) medium, with or without rice tissue. Media containing rice tissue was prepared as previously described [ 25 ]. In brief, flag leaves and panicles of rice cultivars “LYP9” were collected at the late booting stage.…”
Section: Methodsmentioning
confidence: 99%